Particle Board and Oriented Strand Board Prepared with Nanocellulose-Reinforced Adhesive. (3rd June 2012) - Veigel, Stefan; Rathke, Jörn; Weigl, Martin; Gindl-Altmutter, Wolfgang
Abstract : Adhesives on the basis of urea-formaldehyde (UF) and melamine-urea-formaldehyde (MUF) are extensively used in the production of wood-based panels. In the present study, the attempt was made to improve the mechanical board properties by reinforcing these adhesives with cellulose nanofibers (CNFs). The latter were produced from dissolving grade beech pulp by a mechanical homogenization process. Adhesive mixtures with a CNF content of 0, 1, and 3 wt% based on solid resin were prepared by mixing an aqueous CNF suspension with UF and MUF adhesives. Laboratory-scale particle boards and oriented strand boards (OSBs) were produced, and the mechanical and fracture mechanical properties were investigated. Particle boards prepared with UF containing 1 wt% CNF showed a reduced thickness swelling and better internal bond and bending strength than boards produced with pure UF. The reinforcing effect of CNF was even more obvious for OSB where a significant improvement of strength properties of 16% was found. For both, particle board and OSB, mode I fracture energy and fracture toughness were the parameters with the greatest improvement indicating that the adhesive bonds were markedly toughened by the CNF addition.